2015
DOI: 10.4236/jbm.2015.37005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Some Antibiotics in Curing Resistant <i>Escherichia coli</i> Infection

Abstract: There is growing interest in re-evaluation of older antibiotics with the wide spread of pathogen resistance, especially gram negative bacteria, which impair treatment of some infections. In contrast various studies have reported that some antibiotics have efficacy in clearing resistant bacterial infections. On account of that it was interesting to evaluate the efficacy of erythromycin, chloramphenicol and/or tenoxicam in curing and/or relieving wound infection of highly resistant Escherichia coli and investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 131 publications
(126 reference statements)
0
2
0
Order By: Relevance
“…Tenoxicam is a common analgesic and antiinflammatory drug that belongs to the nonsteroidal anti-inflammatory drug class. Tenoxicam was observed to considerably speed up the healing of skin wounds with E. coli infection in vitro in combination with antibiotics, regardless of the bacteria resistance [41][42][43][44]. In a previous study, tenoxicam was reported to have QS inhibitory activity in P. aeruginosa both phenotypically and at the molecular level.…”
Section: Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 99%
“…Tenoxicam is a common analgesic and antiinflammatory drug that belongs to the nonsteroidal anti-inflammatory drug class. Tenoxicam was observed to considerably speed up the healing of skin wounds with E. coli infection in vitro in combination with antibiotics, regardless of the bacteria resistance [41][42][43][44]. In a previous study, tenoxicam was reported to have QS inhibitory activity in P. aeruginosa both phenotypically and at the molecular level.…”
Section: Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 99%
“…In this article, in order to discuss the specific changes of motor cells in the knee osteoarthritis patients under the microscope, we have consulted many relevant resources and summarized them. Among them, El-Banna gave a detailed introduction to the principles of concomitant knee osteoarthritis, analyzed the current problems in the medical system for the treatment of knee osteoarthritis, and elaborated the medical community for knee osteoarthritis Research methods and techniques [3]. In his article, Casula proposed that the development and application of electron microscope technology is very important for the treatment of knee osteoarthritis, and pointed out some of the shortcomings of disciple microscope technology [4].…”
Section: Introductionmentioning
confidence: 99%